Preparation and Physicochemical Stability of Liquid Oral Dosage Forms Free of Potentially Harmful Excipient Designed for Pediatric Patients - Guillaume Binson; Karine Beuzit; Virginie Migeot; Léa Marco; Barbara Troussier; Nicolas Venisse; Antoine Dupuis (MDPI AG, 2019)
Dexamethasone, hydrochlorothiazide, spironolactone, and phenytoin are commonly used in neonates, but no age-appropriate formulation containing these active pharmaceutical ingredients (APIs) is commercially available. Thus, pharmaceutical compounding of the liquid oral dosage form is required to enable newborn administration. A problem common to the compounded preparations described in the literature is that they include potentially harmful excipients (PHEs). Therefore, the aim of this study was to evaluate the feasibility of compounding oral liquid dosage forms free of PHE, containing dexamethasone, hydrochlorothiazide, phenytoin, or spironolactone and to assess their physicochemical stability. Due to the poor water solubility of the targeted APIs, oral suspensions were compounded using Syrspend® SF-PH4 Dry, a suspending vehicle free of PHE. Four HPLC coupled to UV spectrometry (HPLC-UV) stability-indicating methods were developed and validated according to international guidelines to assay the strength of the targeted APIs. Whatever storage condition was used (5 ± 3 °C or 22 ± 4 °C), no significant degradation of API occurred in compounded oral suspensions. Overall, the results attest to the physical and chemical stability of the four oral liquid dosage forms over 60 days under regular storage temperatures. Finally, the use of the proposed oral suspensions provides a reliable solution to reduce the exposure of children to potentially harmful excipients.